Tree-crop Interactions for Below-ground Resources in Drylands: Root Structure and Function - Odhiambo, H O; Ong, C K; Wilson, J; Deans, J D; Broadhead, J; Black, C (Annals of Arid Zone, 2016)
This paper describes recent advances in below-ground research in dryland areas, focusing mainly on studies in dryland Kenya, in which novel sap flow and allometric techniques for determining root structure and function were compared with simple, but labor-intensive methods involving soil coring and trenching. Studies using these approaches indicated that tree (Gliricidia sepium and Grevillea robusta) and. crop (Zea mays) roots predominantly occupied the same soil volume, implying there was little spatial complementarity, and highlighted the existence of considerable variation in tree root density between seasons. The less labor-intensive approach of determining the "competitivity index", based on measurements of main roots, was not a reliable indicator of competition unless it was adjusted for tree size. Fractal relationships provided reasonable estimates of coarse root length, but seriously underestimated the length of fine roots. Sap flow studies showed the marked capacity of tree root activity to switch from one part of the root system to others in response to changes in soil moisture availability, and highlighted the importance of root function as opposed to structure in determining the severity of below-ground competition; such effects may provide both benefits and costs to neighboring plants. Thus, there is an urgent need to develop tree management regimes which promote effective sharing of below-ground resources.